The Role of the Medan State Attorney's Office in Supervising Parole of Prisoners - Ramboo Loly Sinurat; Madiasa Ablisar; Marlina Marlina; Mohammad Ekaputra (Locus Journal of Academic Literature Review, 2023)
The purpose of this study is to determine and analyze the implementation of the Prosecutor's Office in supervising prisoners who receive parole, and the obstacles of the Prosecutor's Office in supervising prisoners who are granted parole. This writing is normative legal writing and the nature of the research is descriptive analytical, the data sources used in this research are primary data and secondary data consisting of primary, secondary and tertiary legal materials. The results of the study concluded that the regulation of parole is regulated in Law Number 12 of 1995 concerning Corrections, Law of the Republic of Indonesia Number 16 of 2004 which was amended to Law of the Republic of Indonesia Number 11 of 2021 concerning the Prosecutor's Office of the Republic of Indonesia, as well as the legal rules for parole based on Regulation of the Minister of Law and Human Rights Number 3 of 2018 concerning Terms and Procedures for Granting Remission, Assimilation, Leave to Visit Family, Parole, Leave Ahead of Release, and Conditional Leave. Supervision can be carried out by the Prosecutor in accordance with the place of residence of the person released on parole. Prosecutors as supervisors in parole of prisoners who obtain parole in the Attorney General's Office, especially in the Medan District Attorney's Office, have obstacles in supervision in parole consisting of internal and external factors.